AN IN-VITRO ANTIBIOFILM ACTIVITY OF CHLORELLA VULGARIS: : Antibiofilm, Quorum sensing, freshwater algae, Chlorella vulgaris, Phytochemicals. - SRIDEVI NS; DHANUSHA V; RAJESWARI M; SANTHI N (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Most of the microbial infection in the body is through biofilm formation. Quorum sensing (QS) is the key regulator in the biofilm formation in both Gram-negative and Gram-positive bacteria. Therefore, interfering with QS is the current strategy to prevent bacterial infection. Methods: In this study, the effect of various extracts of freshwater microalgae – Chlorella vulgaris on the growth of clinical pathogens – Pseudomonas aeruginosa and Staphylococcus aureus which were studied using minimum inhibitory concentration (MIC), antibiofilm activity, and (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) assay using 96-well flat bottom microtiter plates. The phytochemical analysis of C. vulgaris was also carried using standard procedure. Results: The petroleum ether, dichloromethane, chloroform, ethyl acetate, and methanolic and acetone extract of C. vulgaris showed the presence of carbohydrates, amino acids, proteins, steroids, flavonoids, alkaloids, saponins, and phenolic compounds. The MIC value of methanolic extract of C. vulgaris was found to be 1 mg/ml. The highest inhibition of 82.5% and 88.0% was shown by methanolic extract at a concentration of 1 mg/ml for P. aeruginosa and S. aureus, respectively. The antibiofilm activity by crystal violet and MTT assay confirmed the reduction of biofilm formation in both pathogenic organisms. Conclusion: The present results suggested the possible use of C. vulgaris in attenuation of QS and biofilm formation to control pathogenic bacteria – P. aeruginosa and S. aureus.